Eno gredo bom kopala, vsega furma rože sjala - Jakopin, Franc (Traditiones (Ljubljana), 1999)
The author discusses the dialectal expression "furm" (from Ger. Form - Furm; Lat. forma), its different shades of meaning and its use in the texts of 16th century Slovene Protestant writers as well as in Slovene literary and dialectal dictionaries
Keywords: jezikoslovje; linguistics; Slovene; slovenščina; izposojenke; etimologija; etymology